Optimizing the efficiency of perovskite solar cells by a sub-nanometer compact titanium oxide electron transport layer. (July 2018) - Zhang, Jiahuan; Chen, Yaqing; Guo, Wanlin
Abstract: An electron transport layer for electron collection and transport from the perovskite photoactive layer is indispensable in high-performance of mesoscopic perovskite solar cells. A well-organized electron transport layer can significantly improve the quality of the deposited perovskite film, enhance the transport of electrons and help the extraction of electron-hole pairs, but the optimized structural constitution remains elusive. In this work, we find that the optimal performance of perovskite solar cells can be achieved by introducing a sub-nanometer compact titanium dioxide layer to the mesoporous electron transport layers as an ultrathin compact layer is enough to enhance electron extraction and reduce carrier recombination. It is shown that an efficiency around 18% can be reliably achieved at the optimized structural constitution of a 230-nm mesoporous TiO2 layer as well as a compact TiO2 layer in a large equivalent thickness ranging from sub-nanometer to 30 nm. The mesoporous layer is also important as the power conversion efficiencies of all the fabricated perovskite solar cells are less than 11.8% without it. The results shed light on fabrication perovskite solar cells with thinnest compact layer with optimized efficiency. Graphical abstract: fx1 Highlights: By introducing a sub-nanometer compact titanium dioxide layer, PSCs with PCE of 18.3% were obtained. A sub-nanometer compact TiO2 layer efficiently enhances electron extraction of the electron transfer layer. An optimized mp-TiO2 layer results in an increase of 55% in PCE. An efficient c-TiO2 can bring an increase of 123% in PCE.